Paediatric systemic inflammatory response syndrome (SIRS) and the development of patient-specific therapy: ethical perspectives through experts’ opinions - Stolte, Frederik; Aleksandrova-Yankulovska, Silviya; Thiemicke, Paul; Orzechowski, Marcin; Schuetz, Catharina; Steger, Florian (Frontiers in Public Health, 2024)
Background: Research for personalised therapies concerning the Systemic Inflammatory Response Syndrome (SIRS) in children involves the utilisation of OMICs technologies and Artificial Intelligence (AI). Methods: With the aim to identify specific ethical challenges through the perspective of healthcare professionals, we conducted ten semi-structured interviews. The development of questions for the interviews was preceded by a systematic review of the scientific literature. To address the complexities of pediatric emergency research, informed consent and data processing, experts with backgrounds in pediatric intensive care, computer science and medical law were consulted. After transcription and anonymisation, the analysis followed established guidelines for qualitative content and thematic analysis. Results: Interviewees highlighted the intricacies of managing consent in personalised SIRS research due to the large amount and the complexity of information necessary for autonomous decision-making. Instruments to enhance the understanding of legal guardians and to empower the child were therefore appreciated and the need for specific guidelines, and establishing standards, was expressed. Medical risks were estimated low, but challenges of securing anonymisation and data protection were expected. It was emphasised, that risks and benefits cannot be foreseen at this stage. Social justice issues were identified due to possible biases in the research population. Our findings were analysed through the prism of current ethical and legal frameworks for research with a focus on the particularities of the patient group and the emergency background. In this context, experts advocated for an enabling approach concerning AI in combination with OMICs technologies. Conclusion: As with every new technological development, ethical and legal challenges cannot be foreseen for SIRS personalised treatment. That being the case, experts emphasised the importance of extending the ethics-legal discourse beyond mere restrictions. The organisation of supervision should be reconsidered and not limited to the precautionary principle, which per se was seen as impeding the medical progress and clinical flexibility. The establishment and monitoring of guidelines were seen as emergent and should evolve through an interdisciplinary discourse. Therefore, further qualifications of physicians in computer science, the training of AI-developers in ethics and the participation of experts with a background in medical law and data protection were recommended.